1,3-Dihydroxy-9,10-dioxo-9,10-dihydroanthracene-2-carbaldehyde - Pascal Retailleau; Nor Hafizoh Saidan; Rohaya Ahmad; Nor Hadiani Ismail; Khalijah Awang (Acta Crystallographica Section E, 2008)
The title compound, C15H8O5, also known as nordamnacanthal, was isolated from the Malaysian Morinda citrifolia L. The 20 non-H atoms are coplanar. The structure is stabilized by intramolecular O—H...O hydrogen bonds and intermolecular O—H...O and C—H...O hydrogen bonds, forming bilayers of molecular tapes with alternating stacking directions along the a axis.